Ad libitum feeding triggers puberty onset associated with increases in arcuate Kiss1 and Pdyn expression in growth-retarded rats - Sutisa MAJARUNE; Pelden Nima; Arisa SUGIMOTO; Mayuko NAGAE; Naoko INOUE; Hiroko TSUKAMURA; Yoshihisa UENOYAMA (The Society for Reproduction and Development, 2019)
Increasing evidence shows that puberty onset is largely dependent on body weight rather than chronological age. To investigate the mechanism involved in the energetic control of puberty onset, the present study examined effects of chronic food restriction during the prepubertal period and the resumption of ad libitum feeding for 24 and 48 h on estrous cyclicity, Kiss1 (kisspeptin gene), Tac3 (neurokinin B gene) and Pdyn (dynorphin A gene) expression in the hypothalamus, luteinizing hormone (LH) secretion and follicular development in female rats. When animals weighed 75 g, they were subjected to a restricted feeding to retard growth to 70-80 g by 49 days of age. Then, animals were subjected to ad libitum feeding or remained food-restricted. The growth-retarded rats did not show puberty onset associated with suppression of both Kiss1 and Pdyn expression in the arcuate nucleus (ARC). 24-h ad libitum feeding increased tonic LH secretion and the number of Graafian and non-Graafian tertiary follicles with an increase in the numbers of ARC Kiss1- and Pdyn-expressing cells. 48-h ad libitum feeding induced the vaginal proestrus and a surge-like LH increase with an increase in Kiss1-expressing cells in the anteroventral periventricular nucleus (AVPV). These results suggest that the negative energy balance causes pubertal failure with suppression of ARC Kiss1 and Pdyn expression and then subsequent gonadotropin secretion and ovarian function, while the positive energetic cues trigger puberty onset via an increase in ARC Kiss1 and Pdyn expression and thus gonadotropin secretion and follicular development in female rats.